Saving cold drinking water in residential hot water distribution systems - Ioris, Marcelo Dalmédico; Ghisi, Enedir (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
In homes that have instantaneous gas heaters to heat water, cold water is wasted in the first seconds of using hot water fixtures. This waste is caused due to the large lengths of piping between the hot water fixtures and the heater that feeds them. The water in such pipes suffers thermal losses over time. When turning on the fixtures, this drinking water, because it is cold, is rejected by users, especially when using showers. This work deals with the conformation of a system that avoids wasting water in residential hot water services. To establish this conformation, a usual plumbing design was analysed to verify the changes proposed in order to optimise the operation of the system. The gas-heated hot water pipes are currently installed so that the pipes start at the heater and run through the entire house to the hot water fixtures furthest from the heater. It was found that the waste of water in a water fixture decreases if there is the consumption of hot water previously in one of the water fixtures of the house. To avoid this waste, according to the configuration of the current plumbing systems, it is necessary to install an additional set of electronic equipment that automatically redirects the cold water − that would be wasted − to a water tank for later use. The system proposed is composed of a solenoid valve located at the end of the hot water pipe. This valve has the function of letting flow to the water tank the approximate amount of cold water that would be wasted. Through a radio frequency signal sent when a button located near the hot water fixtures is pressed, the system recognises which water fixture was turned on and the approximate amount of cold water that must be released through the valve until the arrival of hot water from the heater. Then, there must be a pipe that collects the water that flows through the solenoid valve. Such pipe will be connected to a vertical pipe, responsible for collecting water from all flats and directing the water to the water tank. The installation of the system is based on the recommendations of the standards used in Brazil and the most frequent configuration found in homes. This work also serves as a guide for installing the system in homes other than the example shown herein.